kim (tk5895) – HW02 – Henry – (54974)
1
This printout should have 14 questions.
Multiplechoice questions may continue on
the next column or page – fnd all choices
beFore answering.
001
10.0 points
±ind all Functions
g
such that
g
′
(
x
) =
x
2
+ 4
x
+ 2
√
x
.
1.
g
(
x
) = 2
√
x
p
1
5
x
2
+
4
3
x
−
2
P
+
C
2.
g
(
x
) =
√
x
p
1
5
x
2
+
4
3
x
+ 2
P
+
C
3.
g
(
x
) =
√
x
(
x
2
+ 4
x
+ 2
)
+
C
4.
g
(
x
) = 2
√
x
(
x
2
+ 4
x
−
2
)
+
C
5.
g
(
x
) = 2
√
x
(
x
2
+ 4
x
+ 2
)
+
C
6.
g
(
x
) = 2
√
x
p
1
5
x
2
+
4
3
x
+ 2
P
+
C
cor
rect
Explanation:
AFter division
g
′
(
x
) =
x
3
/
2
+ 4
x
1
/
2
+ 2
x
−
1
/
2
,
so we can now fnd an antiderivative oF each
term separately. But
d
dx
p
ax
r
r
P
=
ax
r
−
1
For all
a
and all
r
n
= 0. Thus
2
5
x
5
/
2
+
8
3
x
3
/
2
+ 4
x
1
/
2
= 2
√
x
p
1
5
x
2
+
4
3
x
+ 2
P
is an antiderivative oF
g
′
. Consequently,
g
(
x
) = 2
√
x
p
1
5
x
2
+
4
3
x
+ 2
P
+
C
with
C
an arbitrary constant.
002
10.0 points
Consider the Following Functions:
(
A
)
F
1
(
x
) = sin
2
x ,
(
B
)
F
2
(
x
) =
cos 2
x
4
,
(
C
)
F
3
(
x
) =
cos
2
x
2
.
Which are antiderivatives oF
f
(
x
) = sin
x
cos
x
?
1.
none oF them
correct
2.
F
3
only
3.
F
1
and
F
2
only
4.
F
2
and
F
3
only
5.
F
1
and
F
3
only
6.
all oF them
7.
F
1
only
8.
F
2
only
Explanation:
By trig identities,
cos 2
x
= 2 cos
2
x
−
1 = 1
−
2 sin
2
x ,
while
sin 2
x
= 2 sin
x
cos
x .
But
d
dx
sin
x
= cos
x,
d
dx
cos
x
=
−
sin
x .
Consequently, by the Chain Rule,
(
A
) Not antiderivative.
(
B
) Not antiderivative.
(
C
) Not antiderivative.
003
10.0 points
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Documentkim (tk5895) – HW02 – Henry – (54974)
2
Find
f
(
t
) when
f
′
(
t
) =
5
3
cos
1
3
t
−
6 sin
2
3
t
and
f
(
π
2
) = 3.
1.
f
(
t
) = 11 sin
1
3
t
−
9 cos
2
3
t
+ 2
2.
f
(
t
) = 11 cos
1
3
t
−
9 sin
2
3
t
+ 2
3.
f
(
t
) = 5 sin
1
3
t
+ 9 cos
2
3
t
−
4
correct
4.
f
(
t
) = 5 cos
1
3
t
+ 9 sin
2
3
t
−
4
5.
f
(
t
) = 5 sin
1
3
t
+ 3 cos
2
3
t
−
1
6.
f
(
t
) = 5 cos
1
3
t
+ 3 sin
2
3
t
−
1
Explanation:
The function
f
must have the form
f
(
t
) = 5 sin
1
3
t
+ 9 cos
2
3
t
+
C
where the constant
C
is determined by the
condition
f
p
π
2
P
= 5 sin
π
6
+ 9 cos
π
3
+
C
= 3
.
But by known trig values
sin
π
6
= cos
π
3
=
1
2
,
so 7 +
C
= 3. Consequently,
f
(
t
) = 5 sin
1
3
t
+ 9 cos
2
3
t
−
4
.
004
10.0 points
Find
f
(
x
) on
(
−
π
2
,
π
2
)
when
f
′
(
x
) = 7 + 5 tan
2
x
and
f
(0) = 2.
1.
f
(
x
) = 2 + 2
x
+ 5 tan
x
correct
2.
f
(
x
) =
−
3 + 7
x
+ 5 sec
2
x
3.
f
(
x
) = 2
−
2
x
−
5 tan
x
4.
f
(
x
) = 2 + 2
x
+ 5 tan
2
x
5.
f
(
x
) = 7
−
2
x
−
5 sec
x
6.
f
(
x
) =
−
3 + 7
x
+ 5 sec
x
Explanation:
The properties
d
dx
(tan
x
) = sec
2
x,
tan
2
x
= sec
2
x
−
1
,
suggest that we rewrite
f
′
(
x
) as
f
′
(
x
) = 2 + 5 sec
2
x,
for then the most general antiderivative of
f
′
is
f
(
x
) = 2
x
+ 5 tan
x
+
C,
with C an arbitrary constant. But if
f
(0) = 2,
then
f
(0) =
C
= 2
.
This is the end of the preview.
Sign up
to
access the rest of the document.
 Fall '08
 Cepparo
 Calculus, Derivative, Fundamental Theorem Of Calculus, Cos, Constant of integration

Click to edit the document details